Questioning the basic tenets of the American Constitution relating to justice and the rights of citizens in langston hughes’s let America be America again and freedom’s plow - Coulibaly, Zakaria (Humanities & Language: International Journal of Linguistics, Humanities, and Education, 2025)
This article is aimed at demonstrating how the Constitution of the United States has failed to safeguard and protect the basic and inalienable rights of the American citizen, the African American in particular. It also analyzes and interprets the dreams of the American citizens through the perspective of Hughes in his poems. Indeed, at the elaboration and the implementation of the Constitution of the United States with its additional amendments in the 18th century, one of the basic tenets was justice and the protection of all the American citizens regardless of race and gender; however, in the American societies of the 20th century, the inalienable rights of some Americans, mainly Blacks were not granted or protected. Theoretically, critical race theory is used to analyze and interpret the data of the study. The qualitative method is employed in the process of collecting the study’s data. The results of the study have shown that the inalienable rights of the African Americans advocated by the Constitution of the United States and its related amendments were not reflected in society. Indeed, despite their citizenship, their inalienable civil rights were not fully protected, as the majority of them lived on the margins of society. In addition, they were prevented from attending high-profile schools and exercising some occupations reserved for the Whites. The results finally reveal that the dream of the ordinary African Americans was the restoration and the realization of the human rights principles inscribed in the Constitution of the United States through its additional amendments. This would guarantee justice and equal rights for all American nationals regardless of their gender and skin color.